The truth about sports drinks. (18th July 2012) - Cohen, Deborah
Abstract : Sports drinks are increasingly regarded as an essential adjunct for anyone doing exercise, but the evidence for this view is lacking. Deborah Cohen investigates the links between the sports drinks industry and academia that have helped market the science of hydration